Penggunaan Gaya Bahasa pada Promosi Pariwisata Indonesia dalam Iklan Digital Kementerian Pariwisata - Aira Putra Pradana; Chairru Rafi Setyabudi (Tamasya : Jurnal Pariwisata Indonesia, 2025)
Tourism promotion plays a crucial role in attracting domestic and international tourists. One of the strategies used is digital advertising, which employs persuasive language styles. This study aims to analyze the use of language styles in the digital advertisements of the Indonesian Ministry of Tourism and how linguistic elements in these ads influence audience perception. The research method used is literature review and discourse analysis of several digital advertisements published between 2020 and 2023. The results show that digital advertisements from the Ministry of Tourism tend to use hyperbole, repetition, and metaphor to create emotional appeal. These findings can serve as a reference for developing more effective destination marketing communication strategies.